Working children in urban India - Patil, B. R. (Bangalore, 1988)
This book written by Dr. B. R. Patil is based on an intensive survey conducted in Bangalore during 1984-85 covering 600 children working in different occupations. It seeks to analyse the problem of child iabour and provides new insights into the problem, particularly with regard to the aspirations of the working children. The survey. was not a routine kind; the findings formed the basis for drafting the Child Labour (Employment Regulation, Education, Training and Development) Bill, 1985 and also to design an action project for the development of working children. The Bill and the action project form two of the ten chapters the book contains.
Keywords: Children employment